Seasonality and spatial heterogeneity of the surface ocean carbonate system in the northwest European continental shelf. (October 2019) - Hartman, S.E.; Humphreys, M.P.; Kivimäe, C.; Woodward, E.M.S.; Kitidis, V.; McGrath, T.; Hydes, D.J.; Greenwood, N.; Hull, T.; Ostle, C.; Pearce, D.J.; Sivyer, D.; et al.
Abstract: In 2014–5 the UK NERC sponsored an 18 month long Shelf Sea Biogeochemistry research programme which collected over 1500 nutrient and carbonate system samples across the NW European Continental shelf, one of the largest continental shelves on the planet. This involved the cooperation of 10 different Institutes and Universities, using 6 different vessels. Additional carbon dioxide (CO2 ) data were obtained from the underway systems on three of the research vessels. Here, we present and discuss these data across 9 ecohydrodynamic regions, adapted from those used by the EU Marine Strategy Framework Directive (MSFD). We observed strong seasonal and regional variability in carbonate chemistry around the shelf in relation to nutrient biogeochemistry. Whilst salinity increased (and alkalinity decreased) out from the near-shore coastal waters offshore throughout the year nutrient concentrations varied with season. Spatial and seasonal variations in the ratio of DIC to nitrate concentration were seen that could impact carbon cycling. A decrease in nutrient concentrations and a pronounced under-saturation of surface pCO2 was evident in the spring in most regions, especially in the Celtic Sea. This decrease was less pronounced in Liverpool Bay and to the North of Scotland, where nutrient concentrations remained measurable throughout the year. The near-shore and relatively shallow ecosystems such as the eastern English Channel and southern North Sea were associated with a thermally driven increase in pCO2 to above atmospheric levels in summer and an associated decrease in pH. Non-thermal processes (such as mixing and the remineralisation of organic material) dominated in winter in most regions but especially in the northwest of Scotland and in Liverpool Bay. The large database collected will improve understanding of carbonate chemistry over the North-Western European Shelf in relation to nutrient biogeochemistry, particularly in the context of climate change and ocean acidification.